Community, rurality, and older people: Critically comparing older people's experiences across different rural communities. (February 2017) - Doheny, Shane; Milbourne, Paul
Abstract: Recent years have witnessed renewed academic interest in community as both an organizing concept and empirical case study. While previous work on community was largely limited to descriptive accounts of people's interactions in particular places, recent research has provided broader and more critical understandings of community by making connections between social imaginaries and social actions. This paper contributes to this work by applying a multilayered critical theory approach to the study of community. Starting from a general position that views community as a set of cognitively stabilized ideas and expectations, this approach compares discourses at different social levels of community in terms of how they unfold over time. The paper then applies this approach to experiences of community amongst older people in three rural places in England and Wales. Drawing on materials from interviews with older people and stakeholders, the paper explores the extent to which institutional discourses of community include different points of view and interpersonal discourses draw on reflective discourses. The empirical study highlights how community represents both a social system and a space in which individuals learn to live with others in the context of common practices and rule systems. It is also clear from the study that civil society and state actors need to develop new ideas, resources and practices to transform ageing from a demographic descriptor of rural places to an essential component of a shifting rural community discourse. Highlights: We use critical theory to compare older people's experiences across different communities. We develop a cognitivist frame with which to critically compare experiences in different communities. The paper shows how older people's experiences of community are structured by local institutional discourses. The study compares older people's experiences of community in three rural places (two in England, one in Wales).